Rancang Bangun Elektrolit Baterai Menggunakan Cu-Zn dan Air Laut Pantai Kedonganan - Anak Agung Gede Indra Pradipta; Wiko Andrian Winanda; Agus Dharma; Putu Ayu Rhamani Suryadhi (VISA: Journal of Vision and Ideas, 2026)
Indonesia as a maritime country has great potential in utilizing seawater as a renewable energy source, one of which is through seawater battery technology. This study designed and built a battery with seawater-based electrolyte from Kedonganan Beach and Cu-Zn (copper-zinc) electrode pairs for lighting needs. The battery was assembled in a 50×12×8 cm acrylic container, consisting of 20 cells connected in series to produce a total voltage of ±12 V, with each cell having a voltage of 0.8 V. Each cell contains five pairs of 6×5 cm electrodes spaced 4 mm apart and separated by paper as a separator. The test results showed a no-load voltage of 16.23 V and a voltage with a 5 watt load of 7.7 V with a current of 0.0018 A. At a 10 watt load, a voltage of 7.75 V and a current of 0.0023 A were achieved. The battery capacity reached 34.56 mAh during the 12-hour test. The depth of discharge (DoD) was recorded at 70.56%.